Online practices of old Iloilo Facebook page a thematic analysis of posts, 2012-2022 - Trance, Rene C
Context: In the Philippines, a southeast Asian country whose heritage constantly faces risk from disaster, studies on the contributions of online communities for heritage preservation have remained relatively lacking. Purpose : This qualitative study ams to document the activities of Old Iloilo Facebook Group Page from 2012 to 2022 and find out the impact of these activities to community members and to the preservation of local heritage. Research design, procedures, analysis and ethical considerations : Data gathering procedures follow the guidelines prescribed in passive analysis for socilamedia data. Inclusion and exclusion criteria are based on the suggestion of Franz, Marsh, Chen and Teo (2019). Four hundred twenty-seven (427) postings and their corresponding comments from January 2012 to June 2022 re subjected to thematic analysis outlined by Braun and Clarke (2006). Interviews with some online community members are also conducted to validate and enrich research findings as informed by Fine's Theory on Tiny Publics. Two ethical concerns specifically confidentiality and reflexivity are also considered in framing the study and in interpreting study results. Findings : Most postings feature the City Proper district, are in [old] photographs, lack [full] citation of sources, and reveal a fluid definition of heritage, Members engage in activities like Archiving memories and materials, Documenting heritages, Providing heritage updates., Sharing who's who narratives, and Creating heritage-based products. These activities increase awareness on and appreciation of local heritage and its issues, enable members to establish rapport, share knowledge and resource, and re-establish linkage between and among members. In turn, the group page has mobilized members to campaign for marker installation and heritage mapping and discuss actively heritage-related concerns. Recommendations : Study findings point out the need to update and strengthen online community policies through regular face to face meetings, the inclusion of online communities for heritage as part of civil society organizations, and the conduct of workshops responding to the issues and challenges confronting online communities. A sample workshop for teachers is also provided for this purpose.